2021
DOI: 10.4038/sljm.v30i1.232
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of overweight, obesity and metabolic abnormalities among 12-15 year age group in an urban city in Sri-Lanka

Abstract: Objectives: To determine the prevalence of childhood overweight, obesity and metabolic abnormalities among children aged 12-15 years within the schools in Kandy Municipality area, Sri Lanka.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
0
0
Order By: Relevance
“…A recent Sri Lankan survey showed a prevalence of childhood obesity at 10.3% and overweight at 11.3% [4]. A study conducted in the same draining area of Teaching Hospital Peradeniya, where this study was conducted, found a prevalence of 7.81% overweight and 6.79% obesity among a group of school children [5].…”
Section: Introductionmentioning
confidence: 65%
“…A recent Sri Lankan survey showed a prevalence of childhood obesity at 10.3% and overweight at 11.3% [4]. A study conducted in the same draining area of Teaching Hospital Peradeniya, where this study was conducted, found a prevalence of 7.81% overweight and 6.79% obesity among a group of school children [5].…”
Section: Introductionmentioning
confidence: 65%